SAT0325 STELLATE BLOCKADE COMBINED TO ILOPROST AS SUPPORTIVE TREATMENT OPTION IMPROVES PAIN AND ISCHAEMIC SYMPTOMS IN PATIENTS WITH SYSTEMIC SCLEROSIS. (2nd June 2020) - Höcketstaller, F.; Henkemeier, U.; Zimmermann, M.; Burkhardt, H.; Behrens, F.; Drott, U.; Köhm, M.
Abstract : Background: Peripheral ischaemia is a common symptom in systemic sclerosis (SSc) patients with risk of development of digital ulcers (DU). For its treatment, intravenous iloprost is the most effective option. Accompanying pain symptoms worsen the ischaemic symptoms, so a combination with anaesthetic procedures may improve ischaemic status and the subjective sensation of raynaud and pain. The aim of this study was to observe the impact of a combined treatment of iloprost with stellate blockade (ILOST) in improvement of ischaemic symptoms compared to iloprost treatment only (ILO). Objectives: To evaluate efficacy of the ILOST treatment on changes in vascularisation and sensation of patients with SSc and indication for vasodilatative treatment with Iloprost. Methods: Twenty SSc-patients with indication for ILO-treatment (prophylactic or due to digital ulcerations (DU)) will be included in a prospective observational study. Patients will be offered to combine ILO with stellate blockade (ILOST). Beside documentation of disease activity characteristics (mRSS, number of DU, capillary microscopy at baseline, after ILO-treatment and at week 12), patients are assessed using fluorescence-optical imaging (FOI) as innovative method for illustration of changes in microvascularisation and patient reported outcomes (DASH, VAS) at week 12. Results: This interims analysis includes the result of the first 11 patients treated. Mean baseline characteristics (age and gender) are well balanced. Iloprost treatment was initiated due to prophylactic treatment to avoid DU in all patients. 100% of the patients in the ILOST-group were diagnosed as limited SSc compared to 60% in the ILO-group (diffuse type with 40%). All patients showed abnormalities in capillary microscopy (ILOST group: 83, 3% late pattern 16.7% active pattern; ILO group: 80% late pattern, 20% early pattern). MRSS was low in both groups with 1.8, the disease duration in mean 15.3 years in the ILOST-group compared to 13.2 in the ILO-group, respectively. In both groups, no new DU occurred in the 12-week follow-up. Improvement in VAS pain was reported in 83% of the patients in the ILOST group compared to 60% in the ILO group. DASH improved with a mean of 5.5 points in the ILOST group compared to 3 points in the ILO group. FOI was compared individual at both arms in the ILOST group only. The arm with stellatum blockade showed a pronounced increase of FOI signals of 5% in mean whereas the opposite site showed a decrease of the signal shortly after ILO treatment indicating a pronounced increase of vascularisation in the ILOST treated body site. Conclusion: A new treatment approach to improve acute ischaemic symptoms was tested by combining stellate blockade to iloprost treatment. No new DU occurred up to 12 weeks after treatment in all patients of both groups indicating the relevance of iloprost as effective vascular dilatative therapy in SSc. The additional intervention was well tolerated and asked to repeat. Subjective sensation on pain of the hands as well as DASH was improved in the combined group. FOI showed a relevant increase in vascularisation in the blockade arm compared to the opposite site in which signals decreased indicating a stronger effect of the combined treatment for improvement of vascularisation. Disclosure of Interests: Franziska Höcketstaller Grant/research support from: Rheumazentrum Rhein-Main, Ulf Henkemeier: None declared, Michael Zimmermann: None declared, Harald Burkhardt Grant/research support from: Pfizer, Roche, Abbvie, Consultant of: Sanofi, Pfizer, Roche, Abbvie, Boehringer Ingelheim, UCB, Eli Lilly, Chugai, Bristol Myer Scripps, Janssen, and Novartis, Speakers bureau: Sanofi, Pfizer, Roche, Abbvie, Boehringer Ingelheim, UCB, Eli Lilly, Chugai, Bristol Myer Scripps, Janssen, and Novartis, Frank Behrens Grant/research support from: Pfizer, Janssen, Chugai, Celgene, Lilly and Roche, Consultant of: Pfizer, AbbVie, Sanofi, Lilly, Novartis, Genzyme, Boehringer, Janssen, MSD, Celgene, Roche and Chugai, Ulrich Drott: None declared, Michaela Köhm Grant/research support from: Pfizer, Janssen, BMS, LEO, Consultant of: BMS, Pfizer, Speakers bureau: Pfizer, BMS, Janssen, Novartis